C(sp3)–H arylation to construct all-syn cyclobutane-based heterobicyclic systems: a novel fragment collection. Issue 54 (3rd June 2020) - Osberger, Thomas J.; Kidd, Sarah L.; King, Thomas A.; Spring, David R.
Abstract : A Pd-catalysed C–H arylation strategy to generate cyclobutane-based, all- syn heterobicyclic fragments is described. This resulted in a virtual collection of 90 novel compounds with superior complexity and properties compared to existing collections. Abstract : All- syn fused cyclobutanes remain an elusive chemotype and thus present an interesting synthetic challenge. Herein, we report the successful application of Pd-catalysed C(sp 3 )–H arylation of cyclobutane compounds to generate all- syn heterobicyclic fragments using an innovative 'inside-out' approach. Through this strategy we generate a virtual collection of 90 fragments, which we demonstrate to have enhanced three-dimensionality and superior fragment-like properties compared to existing collections.